Modelling and Stress Analysis of Shaft Work Subsidence of Underground Power Transmission Line Tunnel - Thamawong, Kridsada; Raongjant, Werasak (Trends in Sciences, 2022)
This research presents an analysis of soil subsidence around shaft work under its construction process and drilling tunnel by finite element method (FEM). The study is focused on the underground power transmission tunnel in the Chao Phraya River construction project (Southern Bangkok Station to Suksawat Road, Thailand) of the Metropolitan Electricity Authority. This research aims to provide information for designing shaft work and preventing drilling tunnel problems. The research analyzed the soil subsidence around shaft work with 12 m of inside diameter and 1 m of thickness that located 33 m underground during constructing a tunnel chimney by sinking method. It is assumed that the analyzed horizontal reaction is the net resistance of the lateral earth pressure around the shaft work. This study found that the subsidence of soil around shaft work during the construction and drilling process had the value between 0.80 - 53.30 mm. In the part of the base slab, the soil subsidence value is between 3.40 - 16.00 mm. It can be concluded that the top of shaft work during the construction and drilling process had a soil subsidence value of 53.30 mm with dmax/H ratio of 0.00162. HIGHLIGHTS The Metropolitan Electricity Authority has an underground power transmission tunnel in the Chao Phraya River Construction (Southern Bangkok Station to Suksawat Road, Thailand) project which used to distribute electricity from the source station to the other side of the Chao Phraya River This research studied the behavior of the shaft work in sinking reinforced concrete shaft work and drilling tunnel process by finite element method (FEM) with the Midas Gen 2021 program The analysis results of the maximum soil subsidence around the shaft work wall occurred in the top area (very soft to medium stiff clay layer) GRAPHICAL ABSTRACT